2020
DOI: 10.1080/21505594.2020.1809962
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Staphylococcus haemolyticus on primary human skin fibroblast cells

Abstract: Staphylococcus haemolyticus ( S. haemolyticus ) is one of the Coagulase-negative staphylococci (CoNS) that inhabits the skin as a commensal. It is increasingly implicated in opportunistic infections, including diabetic foot ulcer (DFU) infections. In contrast to the abundance of information available for S. aureus and S. epidermidis , little is known about the pathogenicity of S. haemolyticus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 75 publications
1
26
0
1
Order By: Relevance
“…Patients admitted to chest intensive care units are frequently subjected to prolonged antibiotic therapy, which increases the risk of the development of antibiotic resistance, which explains the high rates of antimicrobial resistance observed in our samples [36][37][38][39][40][41]. The increased resistance to multiple antibiotics in Gram-negative bacteria presents significant global health-care problems because these MDR Gram-negative pathogens are often not controlled by the available and effective antibiotics [42][43][44].…”
Section: Discussionmentioning
confidence: 93%
“…Patients admitted to chest intensive care units are frequently subjected to prolonged antibiotic therapy, which increases the risk of the development of antibiotic resistance, which explains the high rates of antimicrobial resistance observed in our samples [36][37][38][39][40][41]. The increased resistance to multiple antibiotics in Gram-negative bacteria presents significant global health-care problems because these MDR Gram-negative pathogens are often not controlled by the available and effective antibiotics [42][43][44].…”
Section: Discussionmentioning
confidence: 93%
“…Methicillin resistance in a growing problem in coagulates positive and negative staphylococci. 60,61 Interestingly, about half of Staphylococci aureus isolated from ambulance vehicles were MRSA. 52 A recent study from our university hospital also reported that all staphylococci isolated from patients with nosocomial pneumonia were methicillin resistant.…”
Section: Discussionmentioning
confidence: 99%
“…Presumptive Staphylococcus haemolyticus colonies on mannitol salt agar and blood agar were initially identified by means of clumping factor test, using the Maststaph™ kit (Mast Group Ltd, Liverpool, UK), further identification and confirmation was achieved by Vitek ® 2 system (BioMerieux, Marcy-I'Etoile, France) 4 to distinguish between Staphylococcus hameolyticus and other coagulase-negative staphylococci of clinical relevance (e.g. S. epidermidis, S. hominis and S. lugdunensis).…”
Section: Isolation and Identification Of Staphylococcus Haemolyticusmentioning
confidence: 99%
“…Staphylococcus haemolyticus is a coagulase-negative common inhabitant of the human skin microbiota that has been recognized as an emerging important opportunistic pathogen 1 . Staphylococcus haemolyticus has been commonly and frequently reported in various nosocomial infections, particularly catheter-associated bacteremia 2 , urinary tract infection 3 , diabetic foot ulcer 4 , device-associated meningitis 5 and wound infections 6 .…”
Section: Introductionmentioning
confidence: 99%